(untitled) (Praxis Educativa, 2012)
This article is about some final reflections of a curricular investigation. We started working with the conceptions our students had at out authority. We could see the focus was on the experts who wrote the school texts and on our own ideas regarding knowledge and authority. We also found out that teachers used mainly school text books lo organize their practice and that they selected them because of the amount of activities they had This "ingenuous" point of view does not consider text books as cultural products. When we analyzed these texts we could see they presented so many contents that they surpassed the number of classes available in a year We could also observe that these contents had no relation with the students cultural experience and that they did not help them develop a reflective comprehension, keeping aside some voices as those of women, ethnic groups, etc.